The Effect of the Self-Questioning Strategy on the Achievement of the Fourth Grade and Their Reflective Thinking in Physics (Journal Of Educational and Psychological Researches, 2023)
Abstract The aim of the research is to identify the effect of using the self-questioning strategy on the achievement of fourth-grade students in science and the development of their reflective thinking in physics in the city of Baghdad. The research sample was divided into two groups: an experimental group of (20) students and a control group of (20) students. The researchers developed two tools: a test of (40) multiple-choice questions. The second tool is a test to measure the reflective thinking skills of fourth-grade students. It consists of (25) multiple-choice questions distributed on skills as follow: reflection and observation, detection of inaccuracies, reaching conclusions, giving clear explanations, and the development of the proposed solutions. The results revealed that there are statistically significant differences at the significance level (0.05) with a degree of freedom (38) between the achievement levels of the students of the two groups in favor of the experimental group. There are statistically significant differences at the significance level (0.05) with a degree of freedom (38) on the critical thinking scale in favor of the experimental group. This confirms that An effective strategy in increasing the achievement and raising the level of reflective thinking among the members of the research sample. In light of the research results, recommendations and suggestions were developed.